STRUKTUR RASA ADORASI - Gunawan, Leo Agung Srie (LOGOS, 2021)
The true religious feeling is rooted in adoration. The taste of adoration is derived from the experience of God which indeed shake one’s soul. On one side, the experience of God leads to the recognition of God as the Great Creator of the universe. In this case, God is experienced as the everything. On the other side, it causes that human being encounters the self-recognition as a helpless creature. One feels as a nothingness of creature here. The feeling of adoration, therefore, has a religious structure in human soul that has a direction to God. As the structure of soul, the adoration is likely to be subjective which means that the subject experiences God (the world of ideas) and at the same time, it is objective that God is experienced by the subject (the real world). The object of the experience of adoration is, particularly, transcendent. Finally, the sense of adoration is needed to revive the living of faith for the believers.